Influence of alumina ratio on reactions at the surface of alite crystals during cooling. (9th December 2021) - Böhm, Matthias; Knöpfelmacher, Aneta
Abstract: Microstructural features of industrial Portland cement clinker samples are presented to illustrate the influence of the clinker melt chemistry on the reactions taking place on the surfaces of alite crystals during cooling at high temperatures. While clinker melts rich in Al2 O3 are usually undersaturated with respect to CaO, leading to corrosion of alite crystals and formation of secondary belite, clinker melts rich in Fe2 O3 are oversaturated with respect to CaO. This leads to a final growth step of alite during cooling, as long as the clinker temperature is still in the stability field of alite (>1250°C). In the first case, the microstructural features of the alite surface permits conclusions on the length of the precooling zone in the rotary kiln, which is closely connected to the flame shape. In the latter case, such conclusions cannot be drawn.